Genome‐Wide Analysis of Copy Number Variation in Latin American Parkinson's Disease Patients. Issue 2 (5th November 2020) - Sarihan, Elif Irem; Pérez‐Palma, Eduardo; Niestroj, Lisa‐Marie; Loesch, Douglas; Inca‐Martinez, Miguel; Horimoto, Andrea R.V.R.; Cornejo‐Olivas, Mario; Torres, Luis; Mazzetti, Pilar; Cosentino, Carlos; Sarapura‐Castro, Elison; Rivera‐Valdivia, Andrea; et al.
ABSTRACT: Background: Parkinson's disease is the second most common neurodegenerative disorder and affects people from all ethnic backgrounds, yet little is known about the genetics of Parkinson's disease in non‐European populations. In addition, the overall identification of copy number variants at a genome‐wide level has been understudied in Parkinson's patients. The objective of this study was to understand the genome‐wide burden of copy number variants in Latinos and its association with Parkinson's disease. Methods: We used genome‐wide genotyping data from 747 Parkinson's disease patients and 632 controls from the Latin American Research Consortium on the Genetics of Parkinson's disease. Results: Genome‐wide copy number burden analysis showed that patients were significantly enriched for copy number variants overlapping known Parkinson's disease genes compared with controls (odds ratio, 3.97; 95%CI, 1.69–10.5; P = 0.018). PRKN showed the strongest copy number burden, with 20 copy number variant carriers. These patients presented an earlier age of disease onset compared with patients with other copy number variants (median age at onset, 31 vs 57 years, respectively; P = 7.46 × 10 −7 ). Conclusions: We found that although overall genome‐wide copy number variant burden was not significantly different, Parkinson's disease patients were significantly enriched with copy number variants affecting known Parkinson's disease genes. We also identified that of 250 patients with early‐onset disease, 5.6% carried a copy number variant on PRKN in our cohort. Our study is the first to analyze genome‐wide copy number variant association in Latino Parkinson's disease patients and provides insights about this complex disease in this understudied population. © 2020 International Parkinson and Movement Disorder Society